Digital Payment Usage and Financial Management Behavior: Evidence from Management Students at FEB UNM - Anwar (PT. Maju Malaqbi Makkarana, 2026)
The rapid development of financial technology has transformed the way university students conduct daily financial transactions. Digital payment systems offer convenience, speed, and accessibility; however, their use may also influence students’ financial management behavior. This study aims to analyze the relationship between digital payment usage and financial management behavior among Management students at the Faculty of Economics and Business, Universitas Negeri Makassar (FEB UNM). The study focuses on how the frequency, ease of use, perceived usefulness, and security of digital payment services contribute to students’ ability to manage expenses, control spending, plan budgets, and make financial decisions. This research employs a quantitative approach by collecting data through questionnaires distributed to Management students. The data are analyzed to identify the influence of digital payment usage on students’ financial behavior. The findings are expected to provide empirical evidence that digital payment usage can affect students’ financial habits, particularly in terms of spending control, budgeting discipline, and transaction awareness. This study contributes to the literature on digital finance and student financial behavior by highlighting the importance of responsible digital payment adoption. Practically, the results may provide insights for universities, students, and financial service providers in promoting financial literacy and healthier financial management practices in the digital era.